Titanium Microalloyed Steel: Fundamentals, Technology, and Products - Mao, Xinping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprehensively reviews the research on Ti microalloyed steel, focusing on development and production technology. It discusses steel composition design and performance, as well as technologies for controlling the microstructure and properties of Ti microalloyed steel during the production process. Ti can significantly improve the properties of steel, but its behavior is more complex and more difficult to control during the production process than that of Nb and V. Covering topics ranging from metallurgy theory to production technology and products, the book serves as a valuable reference resource for researchers, engineers, university teachers and students in the field of steel research.
Introduction -- Chemical metallurgy theory on Ti microalloyed steel -- Physical metallurgy theory on Ti microalloyed steel-dissolving and precipitation of Ti containing phases -- Physical metallurgy theory on Ti microalloyed steel-recrystallization and phase transformation -- Technology of production, microstructure and property control of Ti microalloyed steel -- Design, development and application of Timicroalloyed steel.
Keywords: Metals; Metals and Alloys